Analgesic and Anti-Inflammatory Activities of the Methanolic Stem Bark Extract of Nyctanthes arbor-tristis Linn. (29th July 2013) - Kakoti, Bibhuti Bhusan; Pradhan, Paresh; Borah, Sudarshana; Mahato, Kabita; Kumar, Mritunjay
Abstract : Stem bark of Nyctanthes arbor-tristis Linn. was extracted in methanol to evaluate their analgesic and anti-inflammatory activities. The analgesic activity was determined on Wistar albino rats by hot plate method, tail flick assay, and tail immersion method using Morphine sulphate as standard drug at a dose of 5 mg/kg of body weight and the results were expressed as mean increase in latency after drug administration ± SEM. The anti-inflammatory activity was assessed by Carrageenan-induced rat paw oedema using diclofenac sodium as standard drug at a dose of 100 mg/kg of body weight and expressed in terms of mean increase in paw volume ± SEM. Stem bark extract was given at a dose of 250 mg/kg and 500 mg/kg of body weight. Both standard drugs and extract were administered orally to the animals. Control received distilled water orally. Results showed that Nyctanthes arbor-tristis Linn. had potent analgesic and anti-inflammatory activities.